Economic burden of complications and readmission following oesophageal cancer surgery. Issue 11 (21st September 2022) - Browning, Alison F.; Chong, Lynn; Read, Matthew; Hii, Michael W.
Abstract: Background: Oesophageal cancer is the seventh most prevalent malignancy globally, and the sixth most common cause of cancer‐related death. Oesophageal cancer is also one of the most costly cancers to treat. The aim of this study was to assess the financial impact of post‐operative morbidity and hospital readmissions following oesophagectomy for oesophageal cancer. Methods: A retrospective analysis was performed on a prospectively maintained database of patients with oesophageal cancer who underwent an oesophagectomy at a single centre between July 2014 and June 2019 ( N = 56). Readmission costs were also assessed in this cohort for 12 months post‐operatively. Results: The total median cost for oesophagectomy in this cohort was AU57 250. Major complications occurred in 40% of patients, with a median total admission cost of AU74 606, significantly higher than patients with either minor or no complications (median admission cost of AU52 713, P < 0.001). Patients whose operation was complicated by an anastomotic leak had a higher median admission cost than those without a leak (AU104 328 and AU54 972 respectively, P < 0.001). Cost centres representing the greatest proportion of costs were theatre resources and surgical ward care (medical and nursing). A total of 110 readmissions in 25 patients were recorded in the 12 months post‐operatively, the majority for gastroscopy and dilatation of anastomotic stricture. Conclusion: Post‐oesophagectomy morbidity greatly increases cost of care. In addition to the clinical benefits, interventions to minimize post‐operative complications are likely to result in substantial cost savings. Abstract : This study assessed the cost of complications after surgical management of oesophageal cancer. It found that major complications were associated with a significant increase in costs, as were readmissions after the initial operation.